Musicking in Cyberspace: Creating Music and Fostering Global Community through a Virtual Choir. - Armstrong, Melanie. (2017)
Abstract: This thesis serves as an exploration of collaborative music-making and the emergence of community within cyberspace. Using Eric Whitacre's Virtual Choir as the basis of my inquiry, I examine the unique circumstances of participation in an Internet-based choral ensemble and how such circumstances differ from those of an offline choral ensemble. I highlight the experiences of individual participants, gathered through recent ethnographic research, to demonstrate how a unique set of idealized relationships are enacted through this collaborative project that transcends geographic and cultural boundaries. I argue that these relationships serve as the foundation for a meaningful community and enable participants to gain new understandings about themselves, others, and the world. In this way, the Virtual Choir refutes common assertions that online experience will replace offline experience and that the Internet is serving to isolate us from each other and our worlds. This thesis contributes to the growing academic discourse on open-source collaboration, digital culture, identity formation, and community in cyberspace. These areas have gained prominence in recent years as the Internet and social media have assumed an increasingly integral role in our everyday lives. The Virtual Choir embodies the ideals of cyberspace--intercreativity, open access, and exchange across cultures--and thus proposes a valuable model for collaboration and community in this Digital Age.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Music.; Advisor: Jeffrey Summit.; Committee: David Locke, and Jospeh Auner.; Keywords: Music, and Web studies.